2016
DOI: 10.1007/s12018-016-9208-2
|View full text |Cite|
|
Sign up to set email alerts
|

Locomotive Syndrome: Definition and Management

Abstract: Locomotive syndrome is a condition of reduced mobility due to impairment of locomotive organs. Since upright bipedal walking involves minutely controlled movement patterns, impairment of any aspect of the locomotive organs has the potential to adversely affect it. In addition to trauma, chronic diseases of the locomotive organs, which progress with repeated bouts of acute exacerbations, are common causes of the locomotive syndrome. In Japan’s super-aging society, many people are likely to experience locomotive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
239
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(261 citation statements)
references
References 93 publications
2
239
0
5
Order By: Relevance
“…Over the past century, the average years of life (life expectancy) have been continuously increasing in most 1 3 dysfunction in the elderly [9,10]. The weakness of locomotive components, consisting of bones, joints, muscles and nerves, causes difficulty in standing, walking, running, climbing stairs, and performing other physical functions essential to daily life.…”
Section: Healthy Life Expectancymentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past century, the average years of life (life expectancy) have been continuously increasing in most 1 3 dysfunction in the elderly [9,10]. The weakness of locomotive components, consisting of bones, joints, muscles and nerves, causes difficulty in standing, walking, running, climbing stairs, and performing other physical functions essential to daily life.…”
Section: Healthy Life Expectancymentioning
confidence: 99%
“…There have been a number of studies that indicated the effectiveness of physical intervention in limiting the disability and functional decline of mobility, strength, balance and gait in an aged population with mild to moderate disability [9]. Since its efficacy is limited in people with severe disability, early detection of the locomotive syndrome and early intervention have been advocated.…”
Section: Prevention Of Locomotive Syndrome and Frailtymentioning
confidence: 99%
“…Although both aging processes are detrimental to survival, aging of blood vessels can lead to fatal events, such as cerebral hemorrhage and infarction. In contrast, although aging of the musculoskeletal system (so‐called “locomotive syndrome” in Japan) might lead to functional deterioration, it is not fatal. These phenomena imply that women have a longer unhealthy lifespan compared with men.…”
Section: Long‐term Longitudinal Studies On Agingmentioning
confidence: 99%
“…estimating the number of osteoporosis patients in Japan at over 12.8 million2. The Japanese Orthopaedic Association has defined conditions wherein mobility functions are declined due to locomotive organ impairment, including osteoporosis and osteoarthritis, as “locomotive syndrome”3, and is proactively committed to taking preventive measures and promoting awareness of locomotive syndrome.…”
mentioning
confidence: 99%